Common Principles of Molecular Electronics and Nanoscale Electrochemistry - Bueno, Paulo R. [UNESP] (Amer Chemical Soc, 2018)
The merging of nanoscale electronics and electrochemistry can potentially modernize the way electronic devices are currently engineered or constructed. This Feature offers a conceptual discussion of this central topic, with particular focus on the impact that uniting physical and chemical concepts at the nanoscale could have on the future development of electroanalytical devices.